1994
DOI: 10.1136/bjo.78.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Single intraoperative applications of 5-fluorouracil during filtration surgery: early results.

Abstract: between the sclera and the conjunctival flap, taking care not to expose the cut back edge of the conjunctival flap to the 5-FU soaked sponge. A typical sponge measured 6 mm (length) by 2 mm (width) by 1 mm (thickness). The sponge was removed, resoaked, and replaced every minute up to 5 minutes. The area was then rinsed with 20 ml of balanced salt solution over a period of 30-60 seconds through a Southampton irrigating cannula. Only after this was completed was a third to a half thickness rectangular scleral fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 29 publications
0
27
2
1
Order By: Relevance
“…Superficial punctate keratitis was seen in only one eye (1.3%), This is much lower than the reported incidence of corneal complications (36-64%) in studies using subconjunctival 5 FU (Heuer et al 1986;The Flourouracil Filtering Study Group 1989;Liebmann et al 1991;Thomas 1993) and similar to that reported in other intraoperative 5 FU studies (Lanigan et al 1994;Mora et al 1996) The development of an epithelial defect and subsequent corneal abscess in an eye 4 months after surgery was most likely due to the preexisting ocular surface disorder. The incidence of bleb leaks (5.3%) was lower than the reported incidence of 20-33% for subconjunctival 5 FU administration (The Flourouracil Filtering Study Group 1989;Liebmann et al 1991).…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Superficial punctate keratitis was seen in only one eye (1.3%), This is much lower than the reported incidence of corneal complications (36-64%) in studies using subconjunctival 5 FU (Heuer et al 1986;The Flourouracil Filtering Study Group 1989;Liebmann et al 1991;Thomas 1993) and similar to that reported in other intraoperative 5 FU studies (Lanigan et al 1994;Mora et al 1996) The development of an epithelial defect and subsequent corneal abscess in an eye 4 months after surgery was most likely due to the preexisting ocular surface disorder. The incidence of bleb leaks (5.3%) was lower than the reported incidence of 20-33% for subconjunctival 5 FU administration (The Flourouracil Filtering Study Group 1989;Liebmann et al 1991).…”
Section: Discussioncontrasting
confidence: 38%
“…Feldman et al (1994) reported 85.4% success rates (IOP less than 20 mm Hg, 20% drop from preoperative levels and a visual acuity loss ∞2 Snellen Chart lines) at six months after trabeculectomy with intraoperative 5 FU (50 mg/ml) in a varied group of glaucoma patients. Lanigan et al (1994) have reported success rates of 94% (IOP less than 22 mm Hg) in varied group of glaucoma patients. Egbert et al (1993) reported success rates (IOP less than 22 mm Hg) of 87% in black patients with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Modifications introduced since then such as the introduction of antimetabolites have improved success rates. [8][9][10][11][12][13][14][15] This has been of particular benefit to those patients who were identified as having a higher risk for failure such as those who had had previous surgery, secondary glaucomas, young people, and non-Caucasian populations. It was established early on in its history that trabeculectomy in black subjects failed earlier compared to white subjects, presumably due to a more vigorous fibrotic response in the subconjunctival space.…”
Section: Introductionmentioning
confidence: 99%
“…29 The 1990s were also remarkable for the widespread introduction of anti-scarring agents in trabeculectomy surgery to improve success. 30,31 As a primary or secondary procedure in children, trabeculectomy was still associated with failure in many cases due to excessive scarring. In 1991, Miller and Rice 32 demonstrated that the use of beta radiation as an anti-scarring agent at the time of surgery prolonged trabeculectomy survival in children.…”
Section: Historymentioning
confidence: 99%